Becoming a values-based leader - Johnson, Homer H. (Emerald Publishing Limited : Information Age Pub., 2012)
What is Values-Based Leadership? How does one become a Values-Based Leader? Why Value-Based Leadership? Certainly these are critical questions. It is now widely recognized that effective leaders, from Martin Luther King through political leaders and corporate executives, have a foundation of values that guide their decision-making, and indeed, their life.However, up to this point there has not been a clear definition of Values-Based Leadership, nor has there been a method for developing Values-Based Leaders. This book addresses these issues by defining Values-Based Leadership; by explaining why this form of leadership leads to effective groups, families and organizations; and by providing a process for helping one discover both their life values and their leadership values.Presented in an interesting, and easy-to-read "story format," the book traces the life of the CEO of a major medical supply company who has "burned out" as a leader, and who blames others for his problems. After being told very bluntly by a former mentor that he is the problem, not others, the CEO seeks out the help of an executive coach. Working with the coach he goes through a process by which he rediscovers his purpose in life, as well as his life and leadership values. And through the process he renews his enthusiasm and effectiveness as a leader. The format of the book allows the reader to go through the same step-by-step discovery process as does the central figure in the book, and to move toward becoming an effective and successful Values-Based Leader.Leaders and executives will find the information and discovery process outlined in the book very helpful in clarifying one's purpose and values, and in giving them a foundation on which to lead. The book also may be used as a supplemental text in courses on leadership.